Deletion of luxI increases luminescence of Vibrio fischeri - Kathryn A. Bellissimo; Alecia N. Septer; Cheryl A. Whistler; Coralis Rodríguez; Eric V. Stabb (mBio)
ABSTRACT Bioluminescence in Vibrio fischeri is regulated by a quorum-dependent signaling system composed of LuxI and LuxR. LuxI generates N-3-oxohexanoyl homoserine lactone (3OC6-HSL), which triggers LuxR to activate transcription of the luxICDABEG operon responsible for bioluminescence. Surprisingly, a ∆luxI mutant produced more bioluminescence than the wild type in culture. In contrast, a 4 bp duplication within luxI, resulting in a frameshift mutation and null allele, decreased luminescence tenfold. A second signaling system encoded by ainSR affects bioluminescence by increasing levels of LuxR, via the transcriptional activator LitR, and the N-octanoyl homoserine lactone (C8-HSL) signal produced by AinS is considered only a weak activator of LuxR. However, ainS is required for the bright phenotype of the ∆luxI mutant in culture. When 3OC6-HSL was provided either in the medium or by expression of luxI in trans, all cultures were brighter, but the ∆luxI mutant remained significantly brighter than the luxI frameshift mutant. Taken together, these data suggest that the enhanced bioluminescence due to the LuxI product 3OC6-HSL counteracts a negative cis-acting regulatory element within the luxI gene and that when luxI is absent the C8-HSL signal is sufficient to induce luminescence.IMPORTANCEThe regulation of bioluminescence by Vibrio fischeri is a textbook example of bacterial quorum-dependent pheromone signaling. The canonical regulatory model is that an autoinducer pheromone produced by LuxI accumulates as cells achieve a high density, and this LuxI-generated signal stimulates LuxR to activate transcription of the lux operon that underlies bioluminescence. The surprising observation that LuxI is dispensable for inducing bioluminescence forces a re-evaluation of the role of luxI. More broadly, the results underscore the potential deceptiveness of complex regulatory circuits, particularly those in which bacteria produce multiple related signaling molecules.